Not all that glitters is gold - Rabinovich, Daniel (2022)
This philatelic corner is a tribute to pyrite, a brilliant mineral with attractive geometric shapes that has always excited collectors and geologists worldwide and whose relevance has been captured on the stamps of many countries.